2004
DOI: 10.1016/s0968-0896(04)00315-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acid derivatives with potential anticancer properties??a structure?activity relationship study. Part 1: Methyl, propyl and octyl esters of caffeic and gallic acids

Abstract: Abstract-The antiproliferative and cytotoxic properties of polyphenolic acid derivatives, structurally related with the natural models caffeic and gallic acids, have been tested in human cervix adenocarcinoma cells (HeLa). Simultaneous structural information was obtained for these compounds through theoretical ab initio methods. This study was conducted for the following esters: methyl caffeate (MC, 1), propyl caffeate (PC, 2), octyl caffeate (OC, 3), methyl gallate (MG, 4), propyl gallate (PG, 5) and octyl ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 20 publications
1
69
1
6
Order By: Relevance
“…Several caffeic acid alkyl esters have been reported to possess a wide array of biological activities (24,27). As reported earlier, reactive oxygen species play a significant role in the regulation of tumor cell growth and expression of COX-2 enzyme (28,29).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Several caffeic acid alkyl esters have been reported to possess a wide array of biological activities (24,27). As reported earlier, reactive oxygen species play a significant role in the regulation of tumor cell growth and expression of COX-2 enzyme (28,29).…”
Section: Discussionmentioning
confidence: 83%
“…This indicated that hydrophilicity of these compounds may play a significant role in the antioxidant activity of these compounds. In contrast, the ferulic acid derivatives 15-23 (C 3 -C 12 ) were more active than their long-chain counterparts (22)(23)(24)(25)(26)(27) (Figure 4B). The conformational rigidity of the ferulates was one of the factors reported for their antioxidant activity (23).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, shortening of the side chain resulted in the loss of antiproliferative activity and this was more apparent with the methylation of one or both hydroxyl groups and p-hydroxy substitution as in syringic and sinapic acids. Caffeic and gallic acids are known for their bioactivity related to modulation of carcinogenesis (Gomes et al, 2003;Fiuza et al, 2004). Characterization of phenolic composition of soluble extracts of millet showed that the quantity of caffeic acid of kodo and proso soluble extracts was 7% and 14% of the total hydroxycinnamic acids present, respectively (Chandrasekara & Shahidi, 2011b).…”
Section: Human Colon Adenocarcinoma Cell Proliferation Inhibitionmentioning
confidence: 99%
“…Furthermore, the consumption of a phytochemicalrich diet (fruits and vegetables) decreases the risk of certain types of human cancers [8,9]. Gallic acid (3,4,5-trihydroxybenzoic acid, GA) has been shown to have many biological properties such as antibacterial [10], antifungal and antimalarial [11], antioxidant [12], and antiherpetic action [13]. GA induced apoptosis in human leukemia HL-60RG cells [14], lung cancer cell lines, stomach cancer KATO III, colon adenocarcinoma COLO 205 cell line [15], and rat pheochromocytoma PC12 cells [16].…”
Section: Introductionmentioning
confidence: 99%